Nanotherapeutic derived from multiple bioactive ingredients of natural products: A robust tool for the development of traditional medicine - Mingsheng Chen (Pharmacological Research - Modern Chinese Medicine, 2024)
Several diseases, such as cancer, are not controlled by a single factor and nanotherapeutic derived from multiple bioactive ingredients of natural products (NMBINP) has shown promise therapeutical results recently. Traditional Chinese medicine (TCM) is a therapeutic system, wherein mixtures of natural products mostly act synergistically to modulate multiple targets. Its therapeutic efficacy has been demonstrated in several disease conditions. Despite the unknown panoramic composition and impurity toxicity of TCM, screening for bioactive ingredients from TCM is still a good path for drug discovery owing to its narrow scope. NMBINP is a TCM-inspired nanomedicine established based on the two major advantages of TCM: (1) screening pharmaceutically active molecules from natural products and (2) achieving effective synergistic therapy with multiple targets. Recently, the isolation of bioactive ingredients from TCM and their delivery using nanoparticles have been extensively developed against diverse diseases. NMBINP possesses synergistic therapeutic features of TCM with multiple identified ingredients and its verifiable efficacy demonstrates bright prospects. Further NMBINP exploration can create more effective therapeutics and contribute to better TCM development as NMBINP takes root in TCM. The current review discusses the strengths and deficiencies of TCM, the development of bioactive ingredients isolated from TCM, and NMBINP as a robust tool for developing traditional medicine. Finally, this article is summarized and future perspectives of NMBINP are discussed.